Sex and fertility education in England: an analysis of biology curricula and students' experiences - Maslowski, Katherine; Biswakarma, Rina; Reiss, Michael J.; Harper, Joyce (Journal of biological education, 2024)
Sex and fertility education is essential to enable people to make informed choices. School is an important source of education, so we examined the current curriculum relating to sex and fertility education in England and compared it with students' accounts of their experiences. We analysed the Awarding Body GCSE science and biology specifications (for 14-16 year-olds) and the A-level biology specifications (for 16-18 year-olds), as these related to relationships, sexuality and fertility. An online survey was conducted with 221 16-17 year-old school students to evaluate their views about their sex and fertility education. We found significant variation between the specifications of the Awarding Bodies at both GCSE and A level. Most of the specifications specify sexually transmitted infections (STIs), hormonal aspects of reproduction and contraception. In the school survey, students indicated that topics such as puberty, contraception and STIs were more likely to be learnt in school. However, topics such as endometriosis, menopause and miscarriage were more likely to be learnt outside school. From both our curriculum analysis and student survey we conclude that there are significant gaps in the curriculum with many important topics being neglected.